2012
DOI: 10.1387/ijdb.123503ib
|View full text |Cite
|
Sign up to set email alerts
|

Rediscovering pluripotency: from teratocarcinomas to embryonic stem cells

Abstract: The pluripotent potential of embryonic stem cells has often seen them touted as the future of regenerative medicine. The road to any therapeutic success however, must stretch back to teratocarcinoma, the tumour from which pluripotent stem cells (embryonal carcinoma cells) were first derived. This 2011 meeting in Cardiff acted as a historical perspective from which the impact of embryonal carcinoma cell research on the present pluripotent stem cell landscape could be observed, with many of the early luminaries … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 68 publications
1
8
0
1
Order By: Relevance
“…Using a complete strand of origin information acquired by Holo-Seq total RNA pipeline, we identified 301 (66 known, 235 unannotated) antisense transcripts and analyzed their abundance in ten individual mESCs (Additional file 3 : Table S5; Additional file 1 : Figure S10). For example, the antisense transcript from Zmynd8, at an Oct4-occupied enhancer, has been shown to be an important regulator of mESCs self-renewal [ 25 ] (Fig. 3a ; Additional file 1 : Figure S10 b).…”
Section: Resultsmentioning
confidence: 99%
“…Using a complete strand of origin information acquired by Holo-Seq total RNA pipeline, we identified 301 (66 known, 235 unannotated) antisense transcripts and analyzed their abundance in ten individual mESCs (Additional file 3 : Table S5; Additional file 1 : Figure S10). For example, the antisense transcript from Zmynd8, at an Oct4-occupied enhancer, has been shown to be an important regulator of mESCs self-renewal [ 25 ] (Fig. 3a ; Additional file 1 : Figure S10 b).…”
Section: Resultsmentioning
confidence: 99%
“…However, further GO term analysis showed that top-ranked genes (690 genes ahead of Utf1) are mostly related to fundamental processes ( S11 Fig ), so it was not easy to confirm novel regulators of mouse ES cell self-renewal and pluripotency directly. Through the Kolmogorov–Smirnov test [ 35 ], we found that 10 genes shortlisted by SICER and 44 genes shortlisted by MUSIC showed no significant enrichment at the top of the gene prioritization list of the CRISPR-sgRNA screen (SICER: P<0.703, MUSIC: P<0.293, S12 Fig ), but 46 genes of the 100 genes shortlisted by CLUES were significantly enriched at the top of the gene prioritization list of the CRISPR-sgRNA screen (P<0.002), and seven genes among these had either unknown or not fully confirmed roles in mouse ES cells [ 20 , 21 ] ( Fig 5D ). This result encouraged us to knock out these genes individually in mouse ES cells to confirm their functions.…”
Section: Resultsmentioning
confidence: 99%
“…To further validate the value of CLUES, we prioritized broad enrichment signals of Nanog, Oct4, H3K4me3 and H3K27me3 with CLUES in mouse ES cell and identified novel regulators of mouse ES cell self-renewal and pluripotency with the help of a genome-wide CRISPR/Cas9 negative selection genetic screen. We successfully identified Fam60a, Zmynd8, and Abt1, which are either novel or have unconfirmed roles in mouse ES cells [ 20 , 21 ] as novel regulators of mouse ES cell self-renewal and pluripotency.…”
Section: Introductionmentioning
confidence: 99%
“…ZMYND8 encodes a zinc finger protein with a complex role in maintaining pluripotency. Although only expressed at low levels, either up- or downregulation of ZMYND8 can induce differentiation in ES cells [33]. JARID2 is a component of chromatin modification complex PRC2 in embryonic stem cells and is required for multilineage differentiation.…”
Section: Resultsmentioning
confidence: 99%